Hambatan Pemberian Restitusi Bagi Anak Korban Pencabulan Dalam Putusan Nomor 133/Pid.Sus/2023/PN. Skt - Andini Salma Hapsari; Riska Andi Fitriono (Lembaga Pengembangan Kinerja Dosen, 2024)
With the times, the modus operandi of crime has also evolved. It’s characterized by crime victims who are currently not only limited to adults, but children are also often victims. One of the crimes that often befall children is sexual abuse. Indonesia as a state of law has attempted to protect children from crime, for example by establishing laws and regulations. One form of protection is by providing rights for child victims of criminal acts, one of which is the right to restitution. However, in practice, the provision of restitution hasn’t t been optimally implemented. The purpose of this research is to find out the causes of the provision of restitution that hasn’t been optimally implemented, especially in the case of Decision Number 133/Pid.Sus/2023/PN. This research uses empirical legal research methods with interview data collection techniques. Based on the results of the research, there are two factors that become obstacles in providing restitution for child victims. First, internal factors in the form of the absence of coercive rules if the perpetrator doesn’t pay restitution, administrative requirements for submitting restitution requests that burden the victim, and there are no rules that guarantee restitution is immediately paid by the perpetrator. Second, external factors in the form of the victim's lack of legal awareness and still focusing on punishing the perpetrator.